Experimental Evidence of Long-Lived Electric Fields of Ionic Liquid Bilayers - Belotti, Mattia; Lyu, Xin; Xu, L.; Halat, P.; Darwish, Nadim; Silvester-Dean, Debbie; Goh, Ching; Izgorodina, E.I.; Coote, M.L.; Ciampi, Simone (AMER CHEMICAL SOC, 2021)
Herein we demonstrate that ionic liquids can form long-lived double layers, generating electric fields detectable by straightforward open circuit potential (OCP) measurements. In imidazolium-based ionic liquids an external negative voltage pulse leads to an exceedingly stable near-surface dipolar layer, whose field manifests as long-lived (∼1-100 h) discrete plateaus in OCP versus time traces. These plateaus occur within an ionic liquid-specific and sharp potential window, defining a simple experimental method to probe the onset of interfacial ordering phenomena, such as overscreening and crowding. Molecular dynamics modeling reveals that the OCP arises from the alignment of the individual ion dipoles to the external electric field pulse, with the magnitude of the resulting OCP correlating with the product of the projected dipole moment of the cation and the ratio between the cation diffusion coefficient and its volume. Our findings also reveal that a stable overscreened structure is more likely to form if the interface is first forced through crowding, possibly accounting for the scattered literature data on relaxation kinetics of near-surface structures in ionic liquids.